2021
DOI: 10.1016/j.sjbs.2020.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action and determination of antioxidant activity in the dietary sources: An overview

Abstract: Determination of antioxidant/capacity in the dietary, food, drugs, and biological samples is an interesting approach for testing the safety of these compounds and for drug development. Investigating the google searching engines for the words (measurement + antioxidant + capacity) yielded more than 20 million results, which makes it very difficult to follow. Therefore, collecting the common methods to measure the antioxidant activity/capacity in the food products and biological samples will reduce the burden fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 61 publications
1
74
0
3
Order By: Relevance
“…These mixed mode tests are generally based on the elimination of a stable chromophore (like 2,2′-azinobis-3-ethylbenzthyazolin-6-sulfonic acid) (ABTS) and 2,2-diphenyl-1-picrylhydrazil (DPPH)), where HAT, ET, and proton-coupled electron transfer (PCET) mechanisms may play different roles in varied proportions, depending on the corresponding reaction conditions (such as pH and solvent) [ 66 ]. Mixed mode tests (HAT/SET) mainly include the ABTS/Trolox equivalent antioxidant capacity (TEAC) test, the DPPH radical neutralisation test, and the N,N-dimethyl-p-phenylenediamine dihydrochloride (DMPD) radical neutralisation test.…”
Section: Chemical Tests Determining Antioxidant Activitymentioning
confidence: 99%
“…These mixed mode tests are generally based on the elimination of a stable chromophore (like 2,2′-azinobis-3-ethylbenzthyazolin-6-sulfonic acid) (ABTS) and 2,2-diphenyl-1-picrylhydrazil (DPPH)), where HAT, ET, and proton-coupled electron transfer (PCET) mechanisms may play different roles in varied proportions, depending on the corresponding reaction conditions (such as pH and solvent) [ 66 ]. Mixed mode tests (HAT/SET) mainly include the ABTS/Trolox equivalent antioxidant capacity (TEAC) test, the DPPH radical neutralisation test, and the N,N-dimethyl-p-phenylenediamine dihydrochloride (DMPD) radical neutralisation test.…”
Section: Chemical Tests Determining Antioxidant Activitymentioning
confidence: 99%
“…Note that 6 had lower electronic energy than TS 6 -7 by 1.6 kcal mol −1 . We optimized 7 as a neutral species (8) and a reduced form (9) and was found that both the oxo heptacyclo derivative was more stable than 3 by 14.5 kcal mol −1 and the reduced form was also more stable than 4 by 24.1 kcal mol −1 . The oxidation products 3 and 8 are ether derivatives of tropolones which widely occur in nature [56] and can be synthesized from polyhydroxy benzene derivatives [57].…”
Section: Alizarin Radical Adduct Formationmentioning
confidence: 99%
“…During the last decade, much research has been conducted examining the biological effects of free radicals [1][2][3][4][5][6] and antioxidants [7][8][9]. Free radicals are dangerous for living cells, and therefore compounds that can scavenge them are an interesting subject for experimentation [10].…”
Section: Introductionmentioning
confidence: 99%
“…glutationa peroxidase e superóxido desmutase) e não enzimáticos. Enquanto os antioxidantes de origem exógena podem ser comumente obtidos por meio da dieta (ALAM; BRISTI; RAFIQUZZAMAN, 2013;ALKADI, 2018;SIDDEEG et al, 2020), o que inclui compostos fenólicos, flavonoides, ácidos fenólicos, carotenoides, vitaminas e minerais (HE et al, 2017;NEHA et al, 2019).…”
Section: 23 Processos Oxidativos E Espécies Reativasunclassified
“…Estas podem ocorrer pela inibição da síntese de radicais livres, pela captura dos radicais para que não haja reações em cadeia e consequente desbalanço na concentração de espécies reativas e através da restauração dos elétrons desemparelhados nos orbitais das moléculas dos radicais (NEHA et al, 2019). Diversos produtos naturais se apresentam como fontes promissoras contra o estresse oxidativo, devido à grande diversidade de compostos antioxidantes com capacidade para desativar espécies reativas de oxigênio e nitrogênio (SIDDEEG et al, 2020).Sendo assim, a suplementação alimentar utilizando fontes ricas em compostos antioxidantes apresentam diversos benefícios a saúde, incluindo a prevenção de doenças, como por exemplo o câncer e doenças neurodegenerativas (YANG et al, 2018).…”
Section: 23 Processos Oxidativos E Espécies Reativasunclassified